Evaluation of Class Management in the Learning Process at Primary Educational Institutions - Mubarok, Ramdanil; Juliana, Juliana; Kalsum, Umi (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This study aims to analyze the form of classroom management evaluation, the implementation process, and its implications for the learning process at the elementary education level. Although classroom management is a key factor in the effectiveness of learning, there is still a gap in understanding the optimal evaluation strategy to improve the quality of teacher-student interactions. Therefore, this study seeks to provide deeper insight into the evaluation practices implemented by teachers in managing the classroom. This study uses a descriptive-qualitative approach with the research location at Elementary School 006 North Sangatta, East Kutai. Data were collected through observation, interviews, and documentation to understand classroom management evaluation comprehensively. The study results indicate that classroom management evaluation is carried out through checking student attendance, reprimanding students who are not conducive, seating arrangements, and using oral tests as formative and summative assessments. The evaluation process is done by giving assignments and tests, monitoring student involvement, implementing predetermined evaluation criteria, and developing improvement strategies based on the evaluation results. The implications of this study indicate that classroom management evaluation contributes to increasing learning effectiveness, where teachers can adjust teaching techniques based on student needs and available resources. In addition, the evaluation results help teachers adopt more relevant learning strategies, increase student participation and understanding, and optimize managerial skills in creating a conducive learning environment. These findings emphasize the importance of classroom management evaluation as part of efforts to improve the quality of basic education.